2015
DOI: 10.1111/camh.12092
|View full text |Cite
|
Sign up to set email alerts
|

Review: Comprehensive treatments for youth comorbidity – evidence‐guided approaches to a complicated problem

Abstract: Background: Evidence-based treatments (EBTs) with a single-disorder focus have improved the potential for youth mental health care, yet may be an imperfect fit to clinical care settings where diagnostic comorbidity and co-occurring problems are commonplace. Most EBTs were developed to treat one diagnosis or problem (or a small homogenous cluster), but most clinically referred youths present with multiple disorders and problems. Findings: Three emerging approaches may help address the comorbidity that is so com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(24 citation statements)
references
References 77 publications
0
24
0
Order By: Relevance
“…According to the previously mentioned multilevel meta-analysis [20], treatments of concurrent multiple problems, as opposed to any single targeted problem, showed an effect that was not significantly different from zero at post-treatment or follow-up [20]. Some argue that this could suggest that efforts made to concurrently treat multiple problems have been less effective than focusing more narrowly [30], suggesting new ways to address comorbidity in youths [31][32][33]. In an earlier review of trials of 461 youth psychotherapies, spanning from the 1960-ies and 50 years onward, Weisz and colleagues [20] found that the interventions were usually delivered in settings outside regular clinical practice, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…According to the previously mentioned multilevel meta-analysis [20], treatments of concurrent multiple problems, as opposed to any single targeted problem, showed an effect that was not significantly different from zero at post-treatment or follow-up [20]. Some argue that this could suggest that efforts made to concurrently treat multiple problems have been less effective than focusing more narrowly [30], suggesting new ways to address comorbidity in youths [31][32][33]. In an earlier review of trials of 461 youth psychotherapies, spanning from the 1960-ies and 50 years onward, Weisz and colleagues [20] found that the interventions were usually delivered in settings outside regular clinical practice, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…This is often related to a perceived lack of fit between empirically tested (usually disorder-specific) structured treatments and the vagaries of routine practice (Southam-Gerow et al, 2012). 'Transdiagnostic' protocols have been heralded as a way of addressing this implementation gap, offering a more parsimonious and flexible approach to dealing with real-world challenges of comorbidity and case complexity (Bearman and Weisz, 2015). Transdiagnostic interventions for anxiety and depression have been designed to target common mechanisms of emotion regulation implicated in both syndromes (Newby et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The need for an outcomes based approach to helping children and young people with mental health needs is now widely accepted (Bearman & Weisz, ; Wolpert, Ford, et al., ; Wolpert, Fugard, Deighton, & Gorzig, ) including its role in improving outcomes (Bickman, ). Evidence‐based practice has demonstrated that, even with the most effective interventions such as CBT for anxiety (Reynolds, Wilson, Austin, & Hooper, ), a significant proportion of children and young people do not improve, despite being offered recommended interventions (Weisz et al., ).…”
Section: Introductionmentioning
confidence: 99%